Эффективность местного применения нового апигеля с озонотерапией для лечения и профилактики осложнений дентальной имплантации = Effectiveness of new apigel local application with ozone therapy for dental implantation complications treatment and prevention - Pasechnik, A. V.; Kravchenko, L. S. (Journal of Education, Health and Sport, 2015)
Pasechnik A V, Kravchenko L S. Эффективность местного применения нового апигеля с озонотерапией для лечения и профилактики осложнений дентальной имплантации = Effectiveness of new apigel local application with ozone therapy for dental implantation complications treatment and prevention. Journal of Education, Health and Sport. 2015;5(5):101-108. ISSN 2391-8306. DOI 10.5281/zenodo.17454 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A101-108 https://pbn.nauka.gov.pl/works/559170 http://dx.doi.org/10.5281/zenodo.17454 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015. УДК 616.314-089.843-06-084:615.011 ЭФФЕКТИВНОСТЬ МЕСТНОГО ПРИМЕНЕНИЯ НОВОГО АПИГЕЛЯ С ОЗОНОТЕРАПИЕЙ ДЛЯ ЛЕЧЕНИЯ И ПРОФИЛАКТИКИ ОСЛОЖНЕНИЙ ДЕНТАЛЬНОЙ ИМПЛАНТАЦИИ EFFECTIVENESS OF NEW APIGEL LOCAL APPLICATION WITH OZONE THERAPY FOR DENTAL IMPLANTATION COMPLICATIONS TREATMENT AND PREVENTION А. В. Пасечник, Л. С. Кравченко A V Pasechnik, L S Kravchenko Одесский национальный медицинский университет Odessa National Medical University Summary: The article contains the clinical and laboratory examinations of patients suffering from dental periimplantitis of the 1st and the 2nd class. The patients received new apigel on the injured foci of complications and ozone therapy. There was demonstrated the efficiency of the offered method of treatment and prophylaxis of periimplantitis. There were revealed decline in inflammation markers, bacterial content, free-radical lipid peroxidation, as well as stimulating secretion of lysozyme, secretory immunoglobulin and activity of the antioxidant system, positive influencing on osteoregeneration. There was shown an advantage of the offered method of treatment as compared with traditional therapy, which manifested itself in acceleration of recovery processes in the bone tissue, improvement of osteoregeneration and rapid reduction of clinical signs of local inflammation. Key words: dental periimplantitis, inflammation, microbiocenosis, osteoregeneration, ozone therapy, dental gel Резюме. Статья содержит клинико-лабораторные исследования пациентов с дентальным периимплантитом I и II класса, которым применяли местное лечение на очаги осложнений в виде аппликаций нового апигеля и озонотерапии. Показана эффективность предложенного способа лечения и профилактики периимплантитов по снижению маркеров воспаления, микробной обсемененности, свободно-радикального окисления липидов, а также стимуляции секреции лизоцима, секреторного иммуноглобулина и активности антиокстидантной системы, положительному влиянию на остеорегенерацию. Показано преимущество предложенного способа лечения по сравнению с традиционной терапией, что проявлялось в ускорении репаративно-регенеративных процессов в костной ткани и быстром купировании клинических признаков локального воспаления. Ключевые слова: дентальный периимплантит, воспаление, микробиоценоз, остеорегенерация, озонотерапия, дентальный гель. Резюме. Стаття містить клініко-лабораторні дослідження пацієнтів з дентальним періімплантитом I i II класу, яким застосовували місцеве лікування на вогнище ускладнень у вигляді аплікацій нового апігелю та озонотерапії. Показана ефективність запропонованого способу лікування та профілактики періімплантитів за зниженням маркерів запалення мікробної обсіменінністі, вільно-радикального окиснення ліпідів, а також стимуляцією секреції лізоциму, секреторного імуноглобуліну та активності антиоксидантної системи, позитивним впливом на остеорегенерацію. Показано перевагу запропонованого способу лікування у порівнянні з традиційною терапією, що проявлялося у прискоренні репаративно-регенеративних процесів у кістковій тканині та швидкому купірованні клінічних ознак локального запалення. Ключові слова: дентальний періімплантит, запалення, мікробіоценоз, остеорегенерація, озонотерапія, дентальний гель.